Decision Support to Improve Critical Care Services Documentation in an Academic Emergency Department - Turer, Robert W.; Champion, John C.; Rothman, Brian S.; Dunn, Heather S.; Jenkins, Kenneth M.; Everham, Olayinka; Barrett, Tyler W.; Jones, Ian D.; Ward, Michael J.; Miller, Nathaniel M. (Applied Clinical Informatics, 2022)
Objectives Critical care services (CCS) documentation affects billing, operations, and research. No studies exist on documentation decision support (DDS) for CCS in the emergency department (ED). We describe the design, implementation, and evaluation of a DDS tool built to improve CCS documentation at an academic ED.Methods This quality improvement study reports the prospective design, implementation, and evaluation of a novel DDS tool for CCS documentation at an academic ED. CCS-associated ED diagnoses triggered a message to appear within the physician note attestation workflow for any patient seen in the adult ED. The alert raised awareness of CCS-associated diagnoses without recommending specific documentation practices. The message disappeared from the note automatically once signed. We measured current procedural terminology (CPT) codes 99291 or 99292 (representing CCS rendered) for 8 months before and after deployment to identify CCS documentation rates. We performed state-space Bayesian time-series analysis to evaluate the causal effect of our intervention on CCS documentation capture. We used monthly ED volume and monthly admission rates as covariate time-series for model generation.Results The study included 92,350 ED patients with an observed mean proportion CCS of 3.9% before the intervention and 5.8% afterward. The counterfactual model predicted an average response of 3.9% [95% CI 3.5–4.3%]. The estimated absolute causal effect of the intervention was 2.0% [95% CI 1.5–2.4%] (p = 0.001).Conclusion A DDS tool measurably increased ED CCS documentation. Attention to user workflows and collaboration with compliance and billing teams avoided alert fatigue and ensures compliance.
Keywords: electronic health records; documentation; critical care; emergency medicine; clinical decision support